Fabrication of calix[4]arene/polyurethane for the adsorptive removal of cationic dye from aqueous solutions - Ishak, Syahirah; Rosly, Nor Zida; Abdullah, Abdul Halim; Alang Ahmad, Shahrul Ainliah (Springer, 2023)
Calix[4]arene/polyurethane (C4PU) has been synthesized and characterized as an alternative adsorbent for the adsorption of methylene blue (MB) and malachite green (MG) dyes from the aqueous solution. C4PU was synthesized by reacting p-tert-butyl calix[4]arene with hexamethylene diisocyanate (HMDI) as the cross-linking agent. Different polymer ratios were synthesized, and C4PU-4 shows better adsorption than other ratios. The polymer was characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), Brunauer–Emmett–Teller (BET) analysis, and point of zero charges (pHPZC). The isotherms and kinetics of the adsorption of MB and MG were studied under a range of experimental conditions, including pH, adsorbent dosage, initial dye concentration, and contact time. The adsorption was determined by the adsorption percentage of MB and MG dyes from the solution. The Langmuir isotherm model best describes the adsorption process for both dyes, and it follows a pseudo-second-order kinetic model, with the maximum adsorption capacity (qmax) of MB and MG, respectively, was found to be 1.991 mg·g−1 and 2.240 mg·g−1.